A Bibliometric Analysis of Populism in Turkey - GOKCEKUYU, Ertugrul (OPUS Toplum Araştırmaları Dergisi, 2023)
Populism, as a political concept, has garnered substantial attention emerging as a subject of growing global concern. This bibliometric research seeks to investigate the prominence and trends of populism, with a specific emphasis in academic publications in Turkey indexed in Dergipark. The keyword "populism" emerged as the most effective, leading to the exclusion of other keywords from the analysis. The primary objective of this study is to observe the evolving role in academic publications. This analysis does not seek to comprehend the underlying drivers and consequences of populism on democratic values and institutions. Instead, it aims to contribute to the expanding body of knowledge about populism by providing a comprehensive bibliometric analysis of scholarly works. Drawing upon data retrieved from Dergipark, a prominent repository of academic publications, this study will discern publications on populism and its related subtopics, aiming to identify patterns and shifts over time. As a result, this bibliometric analysis will not only underscore the significance of the concept of populism but also lay a foundation for further in-depth research on the topic. By concentrating on Turkey and utilizing data from Dergipark, this study endeavours to enrich the academic understanding of the rise of populism. Popülizm, siyasi bir kavram olarak küresel düzeyde artan bir endişe kaynağı haline gelmiş ve bu bibliyometrik araştırma ile Dergipark'ta dizinlenen akademik yayınlarda popülizm kavramının zaman içinde nasıl bir evrim geçirdiğini anlamak hedeflenmiştir. "Popülizm" kavramı mevcut diğer arama kavramları arasında en etkili anahtar kelime olarak ön plana çıkmıştır. Bu çalışmanın temel amacı, ülkemizde yayınlanmış akademik makalelerde popülizmin gelişen rolünü çalışmaktır. Analiz, popülizmin demokratik değerler ve toplumsal kurumlar açısından etkilerini anlamayı hedeflememektedir. Bununla beraber araştırma popülizm konusunda kapsamlı bir bibliyometrik analiz sunarak bilgi birikimine katkıda bulunmayı amaçlamaktadır. Dergipark'tan elde edilen verilere dayanarak popülizm ve ilgili alt konulardaki yayınları belirleyerek zaman içindeki anlamsal değişimleri tespit edilmiştir. Bu bibliyometrik analiz yalnızca popülizm kavramının önemini vurgulamakla kalmayacak, aynı zamanda konuyla ilgili daha derinlemesine araştırmalara temel teşkil edecektir. Türkiye'ye odaklanarak ve Dergipark'tan elde edilen verileri kullanarak, bu çalışma popülizmin zaman içinde akademik anlayışı nasıl etkilediğini anlamayı hedeflemektedir.